Implementation of E-Module for Soil Material and Soil Characteristics in the Soil Mechanics Course - Ramzi, Muhammad Zahdian; Handoyo, Santoso Sri (Journal of Engineering Education and Pedagogy, 2024)
The presence of technological innovation in education is an effort to enhance the effective delivery of materials to students. E-modules are one of the technological innovations. In this study, the application of e-modules will be carried out for teaching soil and soil characteristics to determine whether the material in the e-module can assist students in improving their learning outcomes. The method used is the design one group pretest posttest method. Implementation will be conducted by administering pretests and posttests as well as discussing the materials provided in the e-module. Based on the research results, it is shown that the implementation of the e-module, which was carried out using pretests and posttests, resulted in an improvement in students' learning outcomes, as measured by the N-Gain formula. An N-Gain value is considered high if G > 0.7, indicating significant improvement, while if the value of G < 0.3, it indicates low improvement. A value of 0.72 was obtained, which falls into the high category. This means that the implementation of the e-module led to a significant improvement and aided the learning activities related to Soil Mechanics.